2021
DOI: 10.1021/acssynbio.1c00437
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Canthaxanthin-Producing Yeast by Combining Spatiotemporal Regulation and Pleiotropic Drug Resistance Engineering

Abstract: The ketocarotenoid canthaxanthin has important applications in the feed industry. Its biosynthesis using microbial cell factories is an attractive alternative to the current chemical synthesis route. Canthaxanthin-producing Saccharomyces cerevisiae was constructed by introducing the β-carotene ketolase variant OBKTM29 into a β-carotene producer. Subcellular re-localization of OBKTM29 was explored, together with copy number adjustment both in the cytoplasm and on the periplasmic membrane, to accelerate the conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…cerevisiae significantly boosted β-carotene production and secretion, while overexpression of the transcriptional activator PDR3 in the PDR family led to enhanced production of β-carotene, astaxanthin, and canthaxanthin in S. cerevisiae . Our previous study found that overexpressing PDR11 and YOL075C significantly increased the production and secretion of tocotrienols .…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…cerevisiae significantly boosted β-carotene production and secretion, while overexpression of the transcriptional activator PDR3 in the PDR family led to enhanced production of β-carotene, astaxanthin, and canthaxanthin in S. cerevisiae . Our previous study found that overexpressing PDR11 and YOL075C significantly increased the production and secretion of tocotrienols .…”
Section: Introductionmentioning
confidence: 90%
“…16 Overexpression of PDR10, SNQ2, and YOL075C in S. cerevisiae significantly boosted β-carotene production and secretion, 17 while overexpression of the transcriptional activator PDR3 in the PDR family led to enhanced production of β-carotene, astaxanthin, and canthaxanthin in S. cerevisiae. 18 Our previous study found that overexpressing PDR11 and YOL075C significantly increased the production and secretion of tocotrienols. 19 However, the efficiency of the transporters depends on the specific structures of the cargos, so the best transporter(s) for δ-tocotrienol may be different from those for the mixture of tocotrienols.…”
Section: ■ Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The plasma membrane provides storage space for the accumulation of heterologous hydrophobic target compounds (Wu et al, 2017), such as carotenoids (Liu et al, 2016). Targeting the key enzymes to the plasma membrane can effectively alleviate the toxicity of hydrophobic compounds and increase production (Bian et al, 2021;Chen M. et al, 2022). Ye et al (2018) fused a β-carotene ketolase (CrtW) and β-carotene hydroxylase (CrtZ) and targeted the fusion protein to the cell membrane, which resulted in a 215.4% increase in astaxanthin production.…”
Section: Reducing Cytotoxicity Of Triterpenoids and Tetraterpenoidsmentioning
confidence: 99%
“…In addition, due to the unique molecular structure of terpenoids, their chemical synthesis routes often involve tedious synthesis steps, leading to low final yields and environmental concerns . Attempts have been made to synthesize terpenoids by introducing the plant-origin pathway genes into model microbial chassis, such as Escherichia coli , and Saccharomyces cerevisiae. But prokaryotes such as E. coli often have difficulty in expressing P450 enzymes properly, which play important roles in the synthesis of many terpenoids.…”
Section: Introductionmentioning
confidence: 99%